Estimation of Dynamic Nonlinear Rational Expectations Models of Primary Commodity Markets with Private and Government Stockholding - Miranda, Mario J.; Glauber, Joseph W. (The Review of Economics and Statistics, 1993)
Mario J. Miranda, Joseph W. Glauber, Estimation of Dynamic Nonlinear Rational Expectations Models of Primary Commodity Markets with Private and Government Stockholding, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 463-470